What is the best endpoint for assessing environmental risk associated with acidification caused by CO2 enrichment using mussels?. (March 2018) - Passarelli, M.C.; Riba, I.; Cesar, A.; DelValls, T.A.
Abstract: Carbon capture and storage is a technology that has been widely determined to be one of the best choices for the short-term reduction of atmospheric CO2 emissions. The aim of this study was to analyze the effects of CO2 enrichment in the ocean on the mussel species Mytilus galloprovincialis using three different endpoints: mortality, embryo-larval development, and neutral red retention time assays (NRRT). Acute effects were found to be associated with a pH values of 6.0 while citotoxity effects and embryo-larval development were associated with a pH value of 7.0. The NRRT assay and embryo-larval development can be recommended as good endpoints for assessing the environmental risk associated with acidification by CO2 enrichment because they provide sensitive responses on the effects of changes in seawater pH on mussels in a short period of time. Moreover, this study may support policymakers in finding appropriate solutions for the conservation of marine ecosystems. Highlights: The paper uses three endpoints to analyze the impacts of CO2 enrichment on mussels. The results showed significant effects on the mussels associated with low pH values. The increase in p CO2 was strongly correlated with the increase of certain metals. LMS and embryo-larval assays provide sensitive results of ocean acidification.